Twin Resemblance in Muscle HIF-1α Responses to Hypoxia and Exercise - Van Thienen, Ruud; Masschelein, Evi; D'Hulst, Gommaar; Thomis, Martine; Hespel, Peter (Frontiers in Physiology, 2017)
Hypoxia-inducible factor-1 (HIF-1) is a master regulator of myocellular adaptation to exercise and hypoxia. However, the role of genetic factors in regulation of HIF-1 responses to exercise and hypoxia is unknown. We hypothesized that hypoxia at rest and during exercise stimulates the HIF-1 pathway and its downstream targets in energy metabolism regulation in a genotype-dependent manner. Eleven monozygotic twin (MZ) pairs performed an experimental trial in both normoxia and hypoxia (FiO2 10.7%). Biopsies were taken from m. vastus lateralis before and after a 20-min submaximal cycling bout @~30% of sea-level VO2max. Key-markers of the HIF-1 pathway and glycolytic and oxidative metabolism were analysed using real-time PCR and Western Blot. Hypoxia increased HIF-1α protein expression by ~120% at rest versus +150% during exercise (p<0.05). Furthermore, hypoxia but not exercise increased muscle mRNA content of HIF-1α (+50%), PHD2 (+45%), pVHL (+45%; p<0.05), PDK4 (+1200%), as well as PFK-M (+20%) and PPAR-γ1 (+60%; p<0.05). Neither hypoxia nor exercise altered PHD1, LDH-A, PDH-A1, COX-4 and CS mRNA expressions. The hypoxic, but not normoxic exercise-induced increment of muscle HIF-1α mRNA content was about 10-fold more similar within MZ twins than between the twins (p<0.05). Furthermore, in resting muscle the hypoxia-induced increments of muscle HIF-1α protein content, and HIF-1α and PDK4 mRNA content were about 3-4-fold more homogeneous within than between the twins pairs (p<0.05). The present observations in monozygotic twins for the first time clearly indicate that the HIF-1α protein as well as mRNA responses to submaximal exercise in acute hypoxia are at least partly regulated by genetic factors.